2010
DOI: 10.1037/a0019459
|View full text |Cite
|
Sign up to set email alerts
|

Do bantams (Gallus gallus domesticus) experience amodal completion? An analysis of visual search performance.

Abstract: Whereas many mammals (some primates and mice) experience amodal completion, previous data split for avian species. However, experimental procedures have been quite different among the species, and thus a direct comparison of various avian species in the same experimental situation is needed. We tested whether bantams (Gallus gallus domesticus) would complete partly occluded figures using a visual search task on the touch monitor, which was successfully used in our previous study with pigeons. First, we trained… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
12
0

Year Published

2010
2010
2022
2022

Publication Types

Select...
4
3
1

Relationship

0
8

Authors

Journals

citations
Cited by 14 publications
(12 citation statements)
references
References 18 publications
0
12
0
Order By: Relevance
“…The most directly comparable work has been conducted with bantams (Nakamura, Watanabe, Betsuyaku, & Fujita, 2010, 2011; Nakamura, Watanabe, & Fujita, 2014; Watanabe, Nakamura, & Fujita, 2013). Nakamura et al (2010) tested bantams with the same stimuli as Fujita and Ushitani (2005) and found little evidence of perceptual completion. Consistent with this, bantams also show no “continuation illusion” as well (Nakamura et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…The most directly comparable work has been conducted with bantams (Nakamura, Watanabe, Betsuyaku, & Fujita, 2010, 2011; Nakamura, Watanabe, & Fujita, 2014; Watanabe, Nakamura, & Fujita, 2013). Nakamura et al (2010) tested bantams with the same stimuli as Fujita and Ushitani (2005) and found little evidence of perceptual completion. Consistent with this, bantams also show no “continuation illusion” as well (Nakamura et al, 2011).…”
Section: Discussionmentioning
confidence: 99%
“…Some studies, using different stimuli and protocols, have suggested the same general conclusion for both chicks (Lea et al 1996 ) and adult hens (Forkman 1998 ). However, it isn’t clear that the numerous methods used to assess amodal completion in chicks and in adult hens are similar enough to reveal actual cognitive similarities between the two age groups (Nakamura et al 2010 ). Indeed, even humans have difficulty with amodal completion under certain circumstances that pigeons and chickens do not (Nakamura et al 2014 ).…”
Section: Visual Cognition and Spatial Orientationmentioning
confidence: 99%
“…Results from studies of avian species have been mixed. Some research has suggested that amodal completion of occluded portions of objects does not occur in pigeons (Aust and Huber 2006;Cerella 1980;Fujita 2001;Fujita and Ushitani 2005;Sekuler et al 1996;Shimizu 1998;Ushitani and Fujita 2005;Ushitani et al 2001;Watanabe and Furuya 1997) and chickens (Nakamura et al 2010(Nakamura et al , 2011. Other studies, however, have shown that special training or stimuli have enhanced amodal completion in these species (pigeons: Nagasaka et al 2007;chickens: Forkman 1998).…”
Section: Same-object Trialmentioning
confidence: 99%